PENGARUH PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA: PENGARUH PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII SMP NEGERI 7 NANGA PINOH PADA MATERI LENSA OPTIK - Afsari, Mira; Fery Haryadi Saputro, Eko (FKIP UM Pontianak, 2026)
This study aims to determine the effect of Problem-Based Learning (PBL) on students' critical thinking skills. This quantitative study used a quasi-experimental approach and a nonequivalent (pretest-posttest) control group design. The subjects were grades VIII A and VIII B, each comprising 25 students. The object of the study was students' critical thinking skills using Problem-Based Learning (PBL). Data collection techniques used two methods: tests and question sheets. The research instrument used was a descriptive test based on critical thinking indicators administered before and after the treatment. The data analysis technique used was the T-test. Data were analyzed through normality tests, homogeneity tests, and t-tests to examine differences in the results of the two classes. The results showed that students' critical thinking skills in both classes were low before the treatment, with an average pretest score of 46.06 for the control class and 41.39 for the experimental class. After the treatment, there was an increase in critical thinking skills in both classes, but the increase in the experimental class was more significant than in the control class. The average posttest score for the control class increased to 53.26, while for the experimental class it increased to 55.56. The t-test results showed a calculated t-value of 2.01, which is greater than the t-table at a significance level of 0.05. Therefore, Ho is rejected and Ha is accepted. The study concluded that the implementation of the Problem-Based Learning (PBL) model significantly impacted students' critical thinking skills. The PBL model effectively trains students in contextual problem-solving, group discussions, and independent investigations, ensuring that students do not simply passively receive information.